Pengawasan Pemerintah Daerah Terhadap Pengelolaan Sumber Daya Alam (Studi Kasus Tambang Pasir Ilegal di Desa Tamalatea Kecamatan Manuju Kabupaten Gowa) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study purposed to find out local government oversight of the management of natural resources associated with illegal sand mining in Taamalatea Village. This study used descriptive qualitative with six informants. Data collection techniques were  observations and interviews with informants. The results of this study showed that the supervision was not running optimally so that it could not minimize the occurrence of miners who could not get permits. Factors affecting supervision were human resources that were still less effective because the community had low education thus they chose to be miners while community participation had cooperated according to what the government wanted to protect the environment to prevent landslides.